Preventive influence of regular physical exercise on the incidence of common cold - a literature review - Czarnecki, Adam; Nosal, Aleksandra; Galanty-Ochyra, Aleksandra; Zając, Piotr; Węgrzyn, Jan; Fijałkowski, Łukasz; Serwońska, Karolina; Pastuszka, Artur; Jabłońska, Olga (Journal of Education, Health and Sport, 2025)
Introduction and purpose: The common cold is a collection of illnesses caused by various pathogens. It has no definite treatment, therefore common cold prevention should be of utmost importance. Regular, moderate physical activity has been linked with lower incidence of common colds. The aim of this review is to summarize all available knowledge on the influence of regular exercise on the incidence of common cold in human adults. State of knowledge: Randomized controlled trials and epidemiological studies suggest that subjects adhering to WHO’s guidelines for physical activity (MVPA), show significantly reduced susceptibility to common cold infection, and possibly, lower number of sick days compared to sedentary counterparts. There is insufficient data to determine a cause of this phenomenon, however prevailing theories include: increased mucosal immunity, increased NK-cells activity, and hormonal adaptations. High intensity and frequency of the exercise may cause transient suppression of the immune system and leaving an “open window” for opportunistic pathogens. Recent studies suggest that for optimal reduction of common cold infections, low intensity activity for over 358 min/week or moderate intensity activity for over 120 min/ week are recommended. This finding however requires reproduction and validation on more diverse populations. Conclusions: Exercise following the WHO MVPA guidelines reduces incidence of common cold and may reduce the number of sick days. High intensity exercise regimes may lead to temporary suppression of the immune system and increase risk of infection. The relationship between exercise duration, intensity and frequency on occurrence of common cold in adults is significant but requires further study to establish clear recommendations.